NOBLE ENGLISH WOMAN ADELINE PAULINA IRBY ON KOSOVO AND METOHIJA IN SERBIA: One of the kindest persons among English people, the one that was living and dying for Serbian people – Miss Paulina Irby” Ivo Andrić (Baština, 2020)
: This paper is about Adeline Paulina Irby, an English lady. She left deep trace and indelible mark in memory of Serbs from Bosnia and Old Serbia (Kosovo and Metohija). Furthermore, it is focused on her journey through whole “European Turkey” (the Balkans) where she wasacquainted with living conditions of the Christians there. She informed England and the whole western world about it. For that purpose, she travelled through Old Serbia-Kosovo and Metohija. Irby broke all the stereotypes Western World adhered to, in the first place stereotypes about “wild Slaves living in the Balkans”. Irby presented to English reader the whole truth about Serbian nation whose Empire was conquered by Ottomans. Paper is particularly focused on her humanitarian work.
Keywords: Paulina Irby, humanitarian, Ottomans, Serbs, travelling